ChemInform Abstract: Excitation of Nucleobases from a Computational Perspective I: Reaction Paths. Issue 52 (6th December 2016) - Giussani, Angelo; Segarra‐Marti, Javier; Roca‐Sanjuan, Daniel; Merchan, Manuela
Abstract: Review: 8163 refs.].